A Chaundy-Bullard Type Identity and its $q$-analogue (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we use the Chaundy-Bullard combinatorial identity to prove some identities involving the Pochhammer k-symbol. In fact, these contribution generalize the results given in the paper [O. Kouba, \emph{ A Chaundy-Bullard type identity involving the Pochhammer symbol}, J. Indagationes Mathematicae 34 (2023) 186-189; Available online at \url{https://doi.org/10.1016/j.indag.2022.10.009]}. We also give some Chaundy-Bullard type identity verified by the generalized hypergeometric series.
Keywords: Combinatorial identity; Chaundy-Bullard identity; Pochhammer k-symbol; q-analogues; Gamma function; Beta function; hypergeometric.